Transformational piano teaching mentoring students from all walks of life - Polischuk, Derek Kealii (New York, NY Oxford University Press, 2019)
"Transformational Piano Teaching: Mentoring Students from All Walks of Life examines the concept of the piano teacher as someone who is more than just a teacher of a musical skill, but also someone who wields tremendous influence on the development of a young person's artistic and empathic potential, as well as their lifelong personal motivational framework. The specific attributes of today's students are explored, including family and peer influences from interpersonal relationships to social media. Additionally, students from specific circumstances are discussed, including those with special needs such as Autism Spectrum Disorders, ADHD, and Depression. Finally, motivation of a teacher's students is related to a teacher's own motivation in their work, as a cycle of positivity and achievement will be recommended as a way to keep an instructor's work fresh and exciting."--Amazon.com.
The piano teacher as a mentor: an introduction -- Teaching gifted students -- Teaching adult pianists -- Meeting the needs of the recreational student -- Working with pianists with depression -- Working with pianists with high-functioning autism -- Working with pianists with attention deficit hyperactivity disorder -- Teaching undergraduate pianists -- Mentoring graduate student pianists -- Working with international student pianists -- What can we learn from some of history's great piano teachers? -- Bringing it all together: Your studio as a diverse set of individuals -- The motivated and inspired piano teacher.
Includes bibliographical references and index.
Keywords: Piano -- Instruction and study; Mentoring; Music -- Instruction and study -- Psychological aspects